Analisis Kondisi Sosial Dan Ekonomi Pengguna Obat Terlarang di Kecamatan Rambutan Kota Tebing Tinggi - Napitupulu, Faridah Zahra Yassar; Putra, Ilham Mirzaya (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2024)
Drug abuse not only negatively affects individual health, but also creates adverse social and economic impacts. The purpose of this study was to analyze and understand the social and economic conditions of illicit drug use in Rambutan Sub-district, Tebing Tinggi City. This research used a qualitative method with a descriptive approach. Data collection methods through observation and in-depth interviews with as many as 5 informants, Data analysis is carried out through data reduction steps, data presentation, and drawing conclusions from information. This data validity method uses source triangulation. The results showed that the background of users using drugs was due to lack of attention from the family, or because of work stamina. the social conditions of drug users who are still actively using illicit substances often show complex patterns of interaction with their social environment. In addition, the economic conditions of drug users in Kecamatan Rambutan vary, and these differences affect their behavior and interactions with their families and communities. In addition, there are three drug prevention strategies implemented by BNNP, namely: Soft power approach strategy, this strategy emphasizes programs in the fields of prevention, community empowerment, and rehabilitation by involving various elements and components of state institutions and related government agencies. Hard power approach strategy, this strategy is a repressive action through aspects of strict and measurable law enforcement in handling drug syndicate networks. Smart power approach strategy, this strategy utilizes the use of digital information technology. The conclusion of the research is that the Social and Economic Conditions of drug users greatly impact the behavior of individual and family life which creates discomfort, isolation, and becomes a financial burden for the family.